2022
DOI: 10.1038/s41377-022-00714-x
|View full text |Cite|
|
Sign up to set email alerts
|

Deep learning in optical metrology: a review

Abstract: With the advances in scientific foundations and technological implementations, optical metrology has become versatile problem-solving backbones in manufacturing, fundamental research, and engineering applications, such as quality control, nondestructive testing, experimental mechanics, and biomedicine. In recent years, deep learning, a subfield of machine learning, is emerging as a powerful tool to address problems by learning from data, largely driven by the availability of massive datasets, enhanced computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
164
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 386 publications
(164 citation statements)
references
References 426 publications
(380 reference statements)
0
164
0
Order By: Relevance
“…6 . A fair comparison is a well-accepted rule in the optimization and machine learning community, which we also followed in these experiments [ [124] , [125] , [126] , [127] ]. These fair rules can guarantee that the experiments are done under the same settings, and there is no bias towards a specific method in competition [ [128] , [129] , [130] ].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…6 . A fair comparison is a well-accepted rule in the optimization and machine learning community, which we also followed in these experiments [ [124] , [125] , [126] , [127] ]. These fair rules can guarantee that the experiments are done under the same settings, and there is no bias towards a specific method in competition [ [128] , [129] , [130] ].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…As with many other applications of ANNs, it remains unclear to which extent the models trained in a given constellation with certain objects can be transferred to different problems. Presently we leave these methods out of the discussion until their "generalization power" [138] is understood better.…”
Section: Qualitative and Semi-qualitative Methodsmentioning
confidence: 99%
“…Sharifi et al [ 41 ] shown how to diagnose tired and untired feet using digital footprint images. According to Zuo et al [ 42 ], deep-learning technologies have improved optical metrology in recent years. He et al [ 43 ] introduced a number of feature selection techniques for reducing the dimensionality of data.…”
Section: Related Workmentioning
confidence: 99%